The Potential of Agricultural Lands for Conservation of Green Area in Chiang Mai City - Lanchanon, Pradchamas (Journal of Architectural/Planning Research and Studies (JARS), 2022)
Chiang Mai, an important City in the northern part of Thailand, has been changed rapidly because ofurban development. This causes the increase of population and changes in land use, especially the rapiddecrease of agricultural lands which, as a result, affects on the environment and quality of life of people in thecity. The objectives of this research study were to investigate the potential of agricultural lands, the attitude ofthe agriculturist in the area on agricultural lands, and to give suggestions on how to conserve the agriculturallands sustainably by means of field survey, collected secondary data and interview 1,000 agriculturist withการศึกษาศักยภาพแหล่งเกษตรกรรม เพื่อการอนุรักษ์ให้เป็นพื้นที่สีเขียวของเมืองเชียงใหม่The Potential of Agricultural Lands for Conservation of Green Areain Chiang Mai Cityปรัชมาศ ลัญชานนท์Pradchamas Lanchanonคณะสถาปัตยกรรมศาสตร์และการออกแบบสิ่งแวดล้อม มหาวิทยาลัยแม่โจ้ เชียงใหม่ 50290Faculty of Architecture and Environmental Design, Maejo University, Chiang Mai 50290, ThailandE-mail: lanchanon@gmail.com116 JARS 10(2). 2013questionnaires. The potential of agricultural lands was then analyzed by Potential Surface Analysis (PSA) andquantitative data was analyzed in terms of percentage and mean. It was found that the northern and easternplains were appropriate for farming, and the southern plain for horticulture. As for economics and social aspects,it revealed that there were sufficient supporting market for farm products, but the problems was high productioncost and low production price. However, the agriculturists want to conserve their agricultural lands, but they didnot have younger generations to do farming. To conserve the farm lands sustainably, it consisted of the landuse control for conservation of agricultural lands, tax measures, investment funds or cooperative, producttransformed promotion, the development of central markets for agricultural products, the implantation ofland-use awareness to the people and younger generations, the knowledge and information dissimilation tothe agriculturists and agricultural grouping.